The Role of PAI Teachers in Instilling the Spiritual Attitude of Students at SMP Ikhlasiyah Palembang - Mahfudz Mahfudz (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
One of the exciting and important aspects of implementing the 2013 curriculum is the development of students' spiritual attitudes. This curriculum is intended to prepare students with positive characteristics, such as religious character, honesty, tolerance, love for the homeland, etc. The objectives of this curriculum are to the vision of SMP Ikhlasiyah: noble character, achievement and insight into the global environment. The study aims to describe and analyze the strategies of PAI teachers in developing students' spiritual attitudes and the factors that influence PAI teachers' strategies in developing students' spiritual attitudes. The results showed that (1) The strategy of PAI teachers in developing the spiritual philosophy of students of SMP Ikhlasiyah Palembang, namely through habituation to pray after the 0th hour, habituation of the implementation of dhuha and zuhr congregational prayers, then through teacher guidance to students by providing advice or motivation, with the teacher's example, and approach through the story method